Aqueous surface chemistry of gold mesh electrodes in a closed bipolar electrochemical cell. (10th January 2020) - Gamero-Quijano, Alonso; Herzog, Grégoire; Scanlon, Micheál D.
Abstract: The influence of the bipolar electrode on the voltammetry observed with a closed bipolar electrochemical cell (CBPEC) goes far beyond simply conducting electrons between the two electrolyte solutions. The surface of each pole of the bipolar electrode may contain redox active functional groups that generate misleading or interfering electrochemical responses. Herein, a 4-electrode CBPEC configuration was studied with the opposite poles of the bipolar electrode resting in separate aqueous and organic electrolyte solutions. Using gold mesh wire electrodes as the poles, we systematically investigated the many experimental variables that influence the observed voltammetry upon addition of a reductant (decamethylferrocene) to the organic phase. External bias of the driving electrodes forced electrons released by decamethylferrocene at the organic pole to flow along the bipolar electrode and reduce redox active surface functional groups at the aqueous pole, such as oxide or hydroxide groups, or carry out the oxygen reduction reaction (ORR) or hydrogen evolution reaction (HER). The 4-electrode CBPEC configuration diminishes capacitive currents, permitting observation of voltammetric signals from electron transfer processes related to surface functional groups at the aqueous pole at much lower scan rates than possible with working electrodes in conventional 3-electrode electrochemical cells. Surface modification, by oxidative or reductive electrochemical pre-treatment, changes the potential window experienced by the aqueous pole in the 4-electrode CBPEC in terms of its position versus the standard hydrogen electrode (SHE) and dynamic range. In a related observation, the electrochemical responses from the surface functional groups on the aqueous pole completely disappear after oxidative pre-treatment, but remain after reductive pre-treatment. The flow of electrons from decamethylferrocene to the surface of the aqueous pole is limited in magnitude, by the decamethylferrocene concentration, and kinetically limited, due to decamethylferrocene diffusion to the organic pole, in comparison to the infinite supply of electrons delivered to the surface of a working electrode in a 3-electrode cell. This unique feature of the 4-electrode CBPEC facilitates a very gradual evolution of the surface chemistry at the aqueous pole, for example from fully oxidised after oxidative pre-treatment to a more reduced state after repetitive cyclic voltammetry cycling. Perspective applications of this slow, controlled release of electrons to the electrode surface include spectroelectrochemical analysis of intermediate states for the reduction of metal salts to nanoparticles, or conversion of CO2 to reduced products at catalytic sites. The use of indium tin oxide (ITO) electrodes in CBPEC experiments for specific reactions is recommended to avoid misleading or interfering electrochemical responses from redox active functional groups prevalent on metallic surfaces. However, the electronic bridge to implement entirely depends on the reaction under study, as ITO also has drawbacks such as a lack of electrocatalytic activity and the requirement of an overpotential due to its semiconducting nature.